Efektivitas Kompres Hangat Jahe dan Senam Ergonomis Terhadap Penurunan Nyeri Gout Arthritis Pada Lansia di Desa Mojolegi Kecamatan Gading Kabupaten Probolinggo - Erika Dwi Safitri; Dodik Hartono; Achmad Kusyairi (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
uric acid is the result of purine metabolism, it will cause pain and rheumatic pain in the joints. Handling to reduce pain is with warm ginger compresses and rgonomic exercises. The purpose of this study was to analyze the effectiveness of ginger warm compresses and ergonomic exercises on reducing gout arthritis pain in the elderly in Mojolegi Village, Gading District, Probolinggo Regency.This type of research is quasi-experimental with a cross over group design approach. The population of 51 people was selected by purposive sampling technique and obtained 36 respondents who met the inclusion and exclusion requirements of the study. The instrument used is the numerical pain scale observation sheet (NRS). The results showed that the pain scale of ginger warm compresses for period I pre-test was 5.17 post-test 3.00, period II pre-test was 3.94 post-test 2.39. In the ergonomic exercise group, period I pre-test was 5.39 post-test 3.67, period II pre-test was 3.89 post-test 2.61. The results of data analysis obtained valuesρV 0.000 in the warm ginger compress group and the ergonomic exercise group so that it can be concluded that both therapies were equally effective, there was no difference between warm ginger compress and ergonomic exercise in reducing gout arthritis pain in the elderly.Ginger warm compresses and ergonomic exercises are non-pharmacological measures that can be applied to relieve pain and provide a sense of comfort. Thus, implementing these two therapies requires sufficient recovery time (wash out) so that the effects of the first intervention are not carried over to the second intervention.